Mechanistic investigations of photo-driven processes over TiO2 by in-situ DRIFTS-MS : Part 1 - platinization and methanol reforming - Highfield, J. G. (2012)
There is growing interest in the reforming of methanol and other bio-oxygenates as high-density, CO2-neutral, renewable sources of H2. Photocatalysis is worthy of investigation as a potentially economic means to drive such endothermic processes. In this study, in-situ DRIFTS, adapted for optical pumping and coupled to on-line MS, was used to observe the surface of TiO2 (Degussa P25) during photo-metallization from pre-sorbed hexachloroplatinate, at a nominal Pt loading of 1 wt%, and to evaluate photo-reforming of methanol over the resulting Pt/TiO2 composite. The irreversible growth of a quasi-continuum absorption, characteristic of the surface plasmon resonance of zerovalent Pt nanoparticles, along with bands at 2050 and 1830 cm−1 typical of metal-adsorbed CO, indicated that photo-metallization was complete typically within 2 hours. Methanol reforming was photocatalyzed at room temperature but in low quantum efficiency, ϕ ≈ 0.01. However, this was raised substantially, to ϕ ≈ 0.07, simply by the application of mild heating (T ≤ 70 °C). Photo-reforming proceeded at a fixed rate but the H2/CO2 ratio generally exceeded that of the reforming stoichiometry, suggesting some retention of CO2. The photo/thermal synergy was rationalized by model DRIFTS studies, starting from formalin (hydrated formaldehyde), which revealed key features of the mechanism. TiO2 promoted the Cannizzaro disproportionation in the dark, yielding formate and methoxy species already at 40 °C. While methoxy was effectively cycled back to the initial photo-dehydrogenation stage, the slow step was identified as formate decomposition to H2 and CO2. The low value measured for the apparent activation energy (40 kJ mol−1) was taken as supporting evidence for ‘water-assisted destabilization’ of formate, as originally reported by Shido and Iwasawa. No evidence was found for an alternative thermal- or photo-reforming mechanism involving the Pt–COad species.